Implementation of Case Discussion Reflection to Improve Nurse Professionalism: A Literature Review - Ni Made Nopita Wati; Ni Luh Putu Thrisna Dewi; Ketut Lisna Wati; Anak Agung Sri Sanjiwani (KHD Production, 2023)
Patient safety is a global issue. Nurses are expected to enhance their abilities and skills in providing quality and safe healthcare to patients. Case-based reflection is one effective method to improve nurses' understanding of complex clinical situations and enhance their performance in addressing challenges in clinical practice. This study aims to explore implementing case discussion reflection to improve nurse professionalism. The method used in this study was a literature review through electronic databases, including ProQuest, Science Direct, PubMed, and Google Scholar. Inclusion criteria for the literature review process were national and international journals discussing the implementation of case-based reflection in hospitals, nursing professionalism, articles published in the last five years (2018-2022), articles written in Indonesian or English, full-text journal articles, and open access. The electronic database search through ProQuest, Science Direct, PubMed, and Google Scholar yielded 85 articles. After abstract screening and exclusion of articles published before 2018, duplicates/same journals, and irrelevant topics, 21 articles remained. Further screening of all articles resulted in 6 articles that will be reviewed for data extraction. The review findings indicate that through case-based reflection, nurses can expand their knowledge and skills in identifying, evaluating, and managing patient care more effectively. This can positively impact healthcare quality, patient safety, and patient satisfaction with the services provided. Therefore, the implementation of case-based reflection is crucial in enhancing nursing professionalism.